A Citation Study of the Literature of Bibliographical Classification to Determine the Core Aurhors Cited - Afolabi, Michael (Journal of Information and Knowledge, 1983)
A citation analysis of the authors cited in the literature of bibliographical classification at two-year intervals from 1960 to 1980 was made to determine the existence of core authors in the field. When the Bradford distribution was applied to the data on the cited authors, it was observed that only one author was determined as the core author.